Stem cell- derived extracellular vesicles as new tools in regenerative medicine - Immunomodulatory role and future perspectives - Karnas, Elżbieta; Dudek, Patrycja; Zuba-Surma, Ewa K. (Frontiers in Immunology, 2023)
In the last few decades, the practical use of stem cells (SCs) in the clinic has attracted significant attention in the regenerative medicine due to the ability of these cells to proliferate and differentiate into other cell types. However, recent findings have demonstrated that the therapeutic capacity of SCs may also be mediated by their ability to secrete biologically active factors, including extracellular vesicles (EVs). Such submicron circular membrane-enveloped vesicles may be released from the cell surface and harbour bioactive cargo in the form of proteins, lipids, mRNA, miRNA, and other regulatory factors. Notably, growing evidence has indicated that EVs may transfer their bioactive content into recipient cells and greatly modulate their functional fate. Thus, they have been recently envisioned as a new class of paracrine factors in cell-to-cell communication. Importantly, EVs may modulate the activity of immune system, playing an important role in the regulation of inflammation, exhibiting broad spectrum of the immunomodulatory activity that promotes the transition from pro-inflammatory to pro-regenerative environment in the site of tissue injury. Consequently, growing interest is placed on attempts to utilize EVs in clinical applications of inflammatory-related dysfunctions as potential next-generation therapeutic factors, alternative to cell-based approaches. In this review we will discuss the current knowledge on the biological properties of SC-derived EVs, with special focus on their role in the regulation of inflammatory response. We will also address recent findings on the immunomodulatory and pro-regenerative activity of EVs in several disease models, including in vitro and in vivo preclinical, as well as clinical studies. Finally, we will highlight the current perspectives and future challenges of emerging EV-based therapeutic strategies of inflammation-related diseases treatment.